2017
DOI: 10.7189/jogh.07.010905
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review of the evidence regarding the effectiveness of community–based primary health care in improving maternal, neonatal and child health: 5. equity effects for neonates and children

Abstract: BackgroundThe degree to which investments in health programs improve the health of the most disadvantaged segments of the population—where utilization of health services and health status is often the worst—is a growing concern throughout the world. Therefore, questions about the degree to which community–based primary health care (CBPHC) can or actually does improve utilization of health services and the health status of the most disadvantaged children in a population is an important one.MethodsUsing a databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…While previous reviews found that there were effects of home visits or women’s group interventions on mortality overall, they did not detect subgroup differences, and we found that only a few studies on participatory women’s groups linked improved equity in coverage to equity in behaviours or mortality 25 28. This could relate to an inadequacy of conventional methodologies, or an implicit theoretical assumption that equity is achieved once everyone has access, by giving equal freedom of choice to enact healthy behaviours, but not also prioritising equitable realisation of health outcomes 12 49 54. Future studies should focus on CHW interventions’ equity effects across the continuum of care, particularly including mortality 55…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…While previous reviews found that there were effects of home visits or women’s group interventions on mortality overall, they did not detect subgroup differences, and we found that only a few studies on participatory women’s groups linked improved equity in coverage to equity in behaviours or mortality 25 28. This could relate to an inadequacy of conventional methodologies, or an implicit theoretical assumption that equity is achieved once everyone has access, by giving equal freedom of choice to enact healthy behaviours, but not also prioritising equitable realisation of health outcomes 12 49 54. Future studies should focus on CHW interventions’ equity effects across the continuum of care, particularly including mortality 55…”
Section: Discussionmentioning
confidence: 58%
“…Finally, while there is a working assumption that CHWs can redress widespread gaps in formal care in low-resource settings, this review underlines that linkages with the formal health care system are crucial not only in achieving effectiveness but also equity in maternal and newborn health outcomes 12. Past studies of community interventions’ overall effectiveness for maternal and newborn health have found that both home-based care practices and care seeking have generally been improved,49 56 while our review showed that the latter was not achieved as equitably as the former.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations